The role of bariatric surgery and appetite-related hormones metabolism in obesity treatment: a literature review - A. O. Nykonenko; Ye. I. Haidarzhi; O. S. Nykonenko; M. H. Holovko; A. S. Protsenko (Zaporožskij Medicinskij Žurnal)
The most frequently performed surgical interventions in the treatment of obesity are the laparoscopic sleeve gastrectomy (LSG), laparoscopic greater curve plication (LGCP), laparoscopic Roux-en-Y gastric bypass (RYGB). Along with effective weight loss, these operations lead to changes in the production of appetite-related hormones that play an important role in the endocrine regulation of energy metabolism.